Age-correlated changes in the canine oral microbiome - Kislik, Gregory; Zhou, Lin; Rubbi, Liudmilla; Pellegrini, Matteo (Frontiers in Microbiology, 2024)
Canine oral disease has been associated with significant changes in the oral microbiome rather than the presence or absence of individual species. In addition, most studies focus on a single age group of canines and as of yet, the relationship between canine microbiomes and age is poorly understood. This study used a shotgun whole gene sequencing approach in tandem with the Aladdin Bioinformatics platform to profile the microbiomes of 96 companion dogs, with the sourmash-zymo reference database being used to perform taxonomic profiling. Findings showed significant age correlations among 19 species, including positive correlations among several Porphyromonas species and a negative correlation with C. steedae. Although a significant correlation was found between predicted and actual ages, ElasticNet Regression was unable to successfully predict the ages of younger canines based on their microbiome composition. Both microbiome samples and microbial species were successfully clustered by age group or age correlation, showing that the age-microbiome relationship survives dimensionality reduction. Three distinct clusters of microbial species were found, which were characterized by Porphyromonas, Conchiformibius, and Prevotella genera, respectively. Findings showed that the microbiomes of older dogs resembled those that previous literature attributed to dogs with periodontal disease. This suggests that the process of aging may introduce greater risks for canine oral disease.